2016
DOI: 10.1104/pp.15.00972
|View full text |Cite
|
Sign up to set email alerts
|

LobeFinder: A Convex Hull-Based Method for Quantitative Boundary Analyses of Lobed Plant Cells

Abstract: ORCID ID: 0000-0001-5462-524X (J.P.).Dicot leaves are composed of a heterogeneous mosaic of jigsaw puzzle piece-shaped pavement cells that vary greatly in size and the complexity of their shape. Given the importance of the epidermis and this particular cell type for leaf expansion, there is a strong need to understand how pavement cells morph from a simple polyhedral shape into highly lobed and interdigitated cells. At present, it is still unclear how and when the patterns of lobing are initiated in pavement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 44 publications
6
67
0
Order By: Relevance
“…The geometric features of a cell segment that influence the probability that a new lobe will form are not known. There is evidence for a minimal lobe-spacing rule (Staff et al, 2012) and a weak correlation between the initial segment length and the probability of lobe formation (Wu et al, 2016). As expected, we found that lobes could form on segments with varying initial geometries; however, new lobes did not form within recently formed lobes.…”
Section: Development Of An Image-analysis Pipeline To Test For Correlsupporting
confidence: 58%
See 4 more Smart Citations
“…The geometric features of a cell segment that influence the probability that a new lobe will form are not known. There is evidence for a minimal lobe-spacing rule (Staff et al, 2012) and a weak correlation between the initial segment length and the probability of lobe formation (Wu et al, 2016). As expected, we found that lobes could form on segments with varying initial geometries; however, new lobes did not form within recently formed lobes.…”
Section: Development Of An Image-analysis Pipeline To Test For Correlsupporting
confidence: 58%
“…The LobeFinder algorithm serves this purpose (Wu et al, 2016); however, it operates on closed geometric shapes. Using the findpeaks algorithm in Matlab on these segments, we found that lobes began as very small but persistent local deflections in the cell boundary that became progressively larger (Supplemental Fig.…”
Section: Development Of An Image-analysis Pipeline To Test For Correlmentioning
confidence: 99%
See 3 more Smart Citations